(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
This study highlights the disclosure of important segmental information in segmental reports, which is an appropriate tool for investors and other stakeholders where information is presented in a segmented manner, allowing for more accurate analysis to make informed decisions. Under IFRS (8) companies must provide segment disclosures Financial instruments that enable investors to evaluate different sources of risk and income as management does. The researchers reached a set of conclusions, the most important of which is that the sectoral reports are a reflection of the internal reports that were submitted to the main decision maker to evaluate performance and allocate resources. The sectoral reports allow reviewing the operations of the economic unit from the same management perspective. Very reliable because it was used in decision-making and this increases the confidence and credibility of users in financial reports. The researchers also concluded that the essential information in each sector must be disclosed accurately and transparently in order to help users understand the performance of the economic unit through its operational sectors, evaluate its performance and allocate resources to it.